A critical evaluation of the volume, relevance and quality of evidence submitted by the tobacco industry to oppose standardised packaging of tobacco products - Hatchard, Jenny L; Fooks, Gary J; Evans-Reeves, Karen A; Ulucanlar, Selda; Gilmore, Anna B (BMJ open, 2014)
Objectives To examine the volume, relevance and quality of transnational tobacco corporations’ (TTCs) evidence that standardised packaging of tobacco products ‘won't work’, following the UK government's decision to ‘wait and see’ until further evidence is available. Design Content analysis. Setting We analysed the evidence cited in submissions by the UK's four largest TTCs to the UK Department of Health consultation on standardised packaging in 2012. Outcome measures The volume, relevance (subject matter) and quality (as measured by independence from industry and peer-review) of evidence cited by TTCs was compared with evidence from a systematic review of standardised packaging . Fisher's exact test was used to assess differences in the quality of TTC and systematic review evidence. 100% of the data were second-coded to validate the findings: 94.7% intercoder reliability; all differences were resolved. Results 77/143 pieces of TTC-cited evidence were used to promote their claim that standardised packaging ‘won't work’. Of these, just 17/77 addressed standardised packaging: 14 were industry connected and none were published in peer-reviewed journals. Comparison of TTC and systematic review evidence on standardised packaging showed that the industry evidence was of significantly lower quality in terms of tobacco industry connections and peer-review (p<0.0001). The most relevant TTC evidence (on standardised packaging or packaging generally, n=26) was of significantly lower quality (p<0.0001) than the least relevant (on other topics, n=51). Across the dataset, TTC-connected evidence was significantly less likely to be published in a peer-reviewed journal (p=0.0045). Conclusions With few exceptions, evidence cited by TTCs to promote their claim that standardised packaging ‘won't work’ lacks either policy relevance or key indicators of quality. Policymakers could use these three criteria—subject matter, independence and peer-review status—to critically assess evidence submitted to them by corporate interests via Better Regulation processes.